Hadith of Ghadir Al-Ghar - Kazem Shammam, M.D. Fatima (Opción, 2019)
The study aims to investigate the Hadith of Ghadir Al-Ghar via comparative qualitative research methods. As a result, The Hadith of al-Ghadir is a Mutawatir Hadith because it was narrated by 12000 narrators and such a large number did not occur except through the command of Allah Almighty. In conclusion, the day of Al-Ghadir is considered as a demarcation line between the people in the history of the Islamic nation after the Prophet, some of them believed in the Imam Ali's Wilayah over them, and some violated it.